EVALUATION OF ANXIOLYTIC ACTIVITY OF ETHANOLIC EXTRACT OF Phyllanthus niruri LEAVES IN MICE - Savvaser, Spandana; Poojary, Rakshitha; Habibullah, Soubiya Mahnoor; M, Ashoka Shenoy (Indian Journal of Pharmacy & Drug Studies, 2024)
Anxiety has become one of the most prevalent and widely experienced mental illnesses, affecting 7-30% of the world’s population. It is characterized as a distressing psychological state of mind, which is represented by internal feeling of uneasiness, stress and agony. Various theories, including psychodynamic, psychoanalytic, and genetic perspectives, have been proposed to explain the etiology of anxiety disorders. Certain drugs used for treatment of anxiety have side effects and limitation such as sedation, central complexity, and habituation and during withdrawal of drug. Researchers are actively exploring natural remedies, especially medicinal plants, to address anxiety disorders and minimize potential side effects associated with conventional drugs. Hence in the present study we investigate the anxiolytic activity of the plant Phyllanthus niruri leaves in mice using various experimental models such as Elevated Plus Maze and Light And Dark Chamber. In the Elevated Plus Maze (EPM) model, parameters measured included the number of entries in open and closed arms, along with the time spent in each. In the Light and Dark Chamber, measurements encompassed the number of crossings between light and dark sides recorded for 10 minutes, along with the time spent in each side. The administration of the different doses of the plant extract produced significant difference in the locomotor activity of the mice.